2022
DOI: 10.3390/genes14010048
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing of Pakistani Consanguineous Families Identified Pathogenic Variants in Genes of Intellectual Disability

Abstract: Intellectual disability (ID) is a condition of significant limitation of cognitive functioning and adaptive behavior, with 50% of etiology attributed to genetic predisposition. We recruited two consanguineous Pakistani families manifesting severe ID and developmental delay. The probands were subjected to whole exome sequencing (WES) and variants were further prioritized based on population frequency, predicted pathogenicity and functional relevance. The WES data analysis identified homozygous pathogenic varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Johansen et al identified biallelic loss‐of‐function mutations in MBOAT7 as the cause of autosmal recessive intellectual disability (ARID) 12 . Prior research also has demonstrated that individuals with biallelic mutations in the MBOAT7 gene exhibit ID, microcephaly, delayed motor milestone acquisition, seizures, speech difficulty, and occasionally autistic features 4,7,10 . In our patients, the identified variants resides in the fifth domain of the MBOAT7 and is associated with features including ID, microcephaly, aggressive behavior, febrile seizure, and global developmental delay presenting symptoms overlapping with the aforementioned reported patients.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Johansen et al identified biallelic loss‐of‐function mutations in MBOAT7 as the cause of autosmal recessive intellectual disability (ARID) 12 . Prior research also has demonstrated that individuals with biallelic mutations in the MBOAT7 gene exhibit ID, microcephaly, delayed motor milestone acquisition, seizures, speech difficulty, and occasionally autistic features 4,7,10 . In our patients, the identified variants resides in the fifth domain of the MBOAT7 and is associated with features including ID, microcephaly, aggressive behavior, febrile seizure, and global developmental delay presenting symptoms overlapping with the aforementioned reported patients.…”
Section: Discussionmentioning
confidence: 56%
“…12 Prior research also has demonstrated that individuals with biallelic mutations in the MBOAT7 gene exhibit ID, microcephaly, delayed motor milestone acquisition, seizures, speech difficulty, and occasionally autistic features. 4,7,10 In our patients, the identified variants resides in the fifth domain of the…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations